STEROIDAL SAPOGENINS 171 BIOGENESIS OF THE STEROIDAL SAPOGENINS IN AGAVES MANFREDA AND HESAN LUIS POTOSIERALOE - MARKER, RE; LOPEZ, J (BOTANICA-MEX S. A, TEXCOCO, EM, MEX, 1947)
Young plants of Agave atrovirens, Agave bracteosa, Agave endlichiana, Agave stricta, Agave mitraeformis, Manfreda gigantea and Hesperaloe funifera gave only manogenin as their steroidal sapogenin. When the plants reached maturity this was converted into h
J PHYS SOC JPN
Keywords: STEROIDAL SAPOGENINS. 171., BIOGENESIS, STEROIDAL SAPOGENINS, AGAVES MANFREDA, HESPERALOE; QUIMICA; QUIMICA FISICA; QUIMICA AMBIENTAL